Prevalence and risk f actors influencing the development of arterial hypertension in patients with a gout - E. I. Markelova; M. S. Eliseev; T. V. Popkova; E. V. Ilinyh; S. I. Glukhova; V. G. Barskova (Научно-практическая ревматология)
Background. Cardiovascular diseases (CVD) is the leading cause of death for gout. Arterial hypertension is a proven CVD risk factor (CVD-RF).Objective. To assess the factors influencing on development of an arterial hypertension in patients with a gout. Subjects and methods. 286 male patients fulfilling Wallace proposed criteria for gout were included in the study: age 51.2 [42.8; 59.4] years, disease duration - 6.2 [3.8; 12.1] years, number of joints involved during disease course - 7 [4; 12], subcutaneous tophi - in 35% of patients, intraosseous tophi - in 44%, nephrolithiasis - in 69%, abdominal obesity - in 71%. All patients underwent standard clinical examination, C-reactive protein (CRP), total cholesterol, triglycerides, low and high density lipoproteins, serum uric acid, serum creatinine, smoking, family history of arterial hypertension, body mass index (BMI), diabetes mellitus was performed by standard procedure. We estimated the adjusted odds ratio (OR) and 95% confidence interval (95% CI).Results. There were two groups of patients with arterial hypertension diagnosed on clinical data: group 1 (with arterial hypertension) - 244 (85%) patients, group 2 (without arterial hypertension) - 42 (15%) patients. The group 1 patients were older (52.3 [44.5; 61.1] vs 41.9 [38.3; 50.1] years old), had longer duration of gout (6.7 [3.9; 13.7] vs 4.5 [3; 7.9]), a higher number of joints involved during disease course (8 [4; 12] vs 5 [3; 9]). The frequency of family history of arterial hypertension (68.3 vs 48.8%), abdominal obesity (55.3 vs 33.3%), nephrolithiasis (71 vs 54.7%), intraosseous tophi (48 vs 21%) was higher in group 1 as compared with group 2, р<0,05. BMI and CRP level was higher in group 1 compared with group 2: 30.2 [27.4; 33.1] vs 27.9 [26.3; 30.5] kg/m2, and 12.7 [5.84; 19.2] vs 7.8 [3.7; 16.4] mg/l, respectively, p<0.05. We did not find differences of lipid profile, serum uric acid, and serum creatinine level in groups 1 and 2. We also did not find differences the frequency of smoking, diabetes mellitus, subcutaneous tophi in both groups.Abdominal obesity (OR - 1.247; 95% CI: 1.063-1.462), family history of arterial hypertension (OR - 2.8; 95% CI: 1.5-5.4), disease duration more than 10 years (OR - 4.5; 95% CI: 1.1-19.4), intraosseous tophi (OR - 3.0; 95% CI: 1.4-6.4), increased the risk for arterial hypertension in patients with a gout.Conclusion. The majority (85%) of patients with gout had arterial hypertension. Abdominal obesity, family history of arterial hypertension, disease duration more than 10 years, intraosseous tophi were associated with an increased risk of arterial hypertension in patients with a gout.